????? ????? ?????? ????? ????? ???????? ????????? TEACHING OF SPEAKING SKILL AT TA'DIB AS-SYAKIRIN ISLAMIC BOARDING SCHOOL IN MEDAN - Maria Ulfa Lubis; Zulpina (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2021)
Abstract: This study aims to determine how the application, objectives, functions, learning methods, learning steps, material taught, supporting and inhibiting factors, as well as problems experienced by the teacher while teaching Maharah Kalam at the Ta'dib Asy-Syakirin Islamic Boarding School, Medan. . The research method used is descriptive qualitative research methods. The results showed that the learning of Maharah Kalam at the Ta'dib Asy-Syakirin Islamic Boarding School was significant in changing the behavior of students towards the learning outcomes achieved, as well as the teachers who were generally professionals. Keyword: Maharah al-Kalam, learning, Arabic Language ???? ??? ??????? ??? ????? ????? ??????? ???????? ???????? ???? ?????? ??????? ??????? ???? ??? ??????? ???????? ??????? ????????? ???????? ??? ???????? ???? ??????? ?????? ????? ????? ????? ?????? ????? ????? ???????? ?????????. ??? ???? ????? ???????? ?? ????? ????? ?????? ??????.????? ??????? ?? ????? ????? ???? ????? ????? ???????? ????????? ??? ????? ?? ????? ???? ?????? ???? ????? ?????? ??????? ? ????? ???????? ????? ????? ?????? ???????